Innovative utilization of chicken feet bones (Gallus gallus domesticus) and mung beans (Vigna radiata) in crackers: A sustainable nutritional approach to combat childhood malnutrition - Malakiano, Anghia Callista Vaci; Arista, Nor Isnaeni Dwi; Akhsanitaqwim, Yochidamai (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Malnutrition leads to weakened immunity, making children more susceptible to infectious diseases and affecting future generations if not promptly addressed. Chicken feet bones (Gallus gallus domesticus) are a food waste product rich in calcium, while mung beans (Vigna radiata) are high in vitamins and minerals, making them potential sources of additional nutrition. This study aims to investigate the processing of Hi-C Crackers using chicken feet bones and mung beans, analyze its macronutrient content qualitatively, and determine its calcium content qualitatively. Methods: This experimental research involved processing Hi-C Crackers and analyzing their nutritional composition qualitatively. Findings: Hi-C Crackers were successfully processed using a 2:1 ratio of chicken feet bones to mung beans. The macronutrient content was determined using qualitative reagent tests: Lugol's iodine test for carbohydrates (blue-black color), Biuret test for protein (purple color), and Benedict’s test for glucose (greenish-blue color). Calcium content was confirmed using ammonium oxalate and acetic acid reagents, producing a brownish-white precipitate. Conclusion: Hi-C Crackers is a nutritious snack with essential macronutrients and calcium. Novelty: This research introduces a new food innovation utilizing commonly discarded ingredients to combat malnutrition.